Eating disturbance and incest - Wonderlich, Stephen; Donaldson, Mary A.; Carson, David K.; Staton, Dennis; Gertz, Linda; Leach, Laurie R. (Journal of interpersonal violence, 1996)
This study examines the relationship between reported history of incest and the subsequent development of bulimic behavior. A total of 38 women receiving treatment for reported incest abuse were compared with 27 control subjects who were also in treatment but who denied histories of sexual abuse. The results revealed that incest victims were significantly more likely to binge, vomit, experience a loss of control over eating, and report body dissatisfaction than control subjects. Incest victims also more frequently showed comorbidity with other maladaptive behaviors, such as alcohol abuse, suicidal gestures, self-mutilation, and cigarette smoking. These results suggest that incest may increase the risk for the development of bulimic behavior and that these eating problems may be a part of a larger pattern of dysfunctional efforts to regulate trauma-related emotional distress